Pengaruh Influencer dan Inovasi Produk Terhadap Keputusan Pembelian Kahf dengan E-Commerce sebagai Moderating - Subianto, Dwi; Basuki, Kustiadi (Universitas Batanghari Jambi, 2024)
This study aims to determine the effect of influencers and product innovation on Kahf buying decisions with e-commerce as moderating. Data analysis used the SmartPLS version 4.0 tool with a sample size of 154 respondents. The population in this study are consumers in North Jakarta with purposive sampling. The results in this study are that influencers and innovations have a significant and positive influence on purchasing decisions. E-commerce as moderation strengthens the relationship between influencers and purchasing decisions. E-commerce as a moderator weakens the relationship between product innovation and purchasing decisions.